Preparation Of Tin Selenide Thin Film Semiconductor By Electrochemical Deposition And Electroselenisation - Ali, Ali Jimale (2000)
Electrochemical preparation of tin selenide thin film semiconductor for photoelectrochemical cells (PECs) was studied. The film has been potentiostatically deposited on tin substrate at room temperature from aqueous solution containing SnCl2 and Na2SeO3. The effect of the electrodeposition potentials and bath electrolytes concentrations proportion were investigated to determine the optimum condition for electrodeposition. The structure, morphology and the photosensitivity of the electrosynthesised samples were studied by using X-ray diffiaction, scanning electron microscopy (SEM) and linear sweep voltammetry techniques. The bandgap energy and type of optical transition were determined from optical absorbance data. The X-ray diffraction analysis confirmed the formation of polycrystalline SnSe on the tin substrate. Scanning electron microscopy reaffirmed the existence of a crystalline deposit with different grain size and shape. The films prepared in this study showed a p-type semiconductor behaviour with very good photosensitivity.